1989
DOI: 10.4098/at.arch.89-2
|View full text |Cite
|
Sign up to set email alerts
|

Origin and history of the present rodent fauna in Poland based on fossil evidence

Abstract: The variability in the mandible dimensions has been investigated in bats of the genus Plecotus Geoffroy, 1818 from Central Europe. The material consisted of 100 individuals of P. auritus and 100 individuals of P. austriacus. The variability in the mandible length appeared to be relatively low in both species (Cv = 3.41-3.99), whereas that in the height of the ramus mandibulae was slightly higher (Cu = 4.93-8.62). For both species the common values of the measurements of the mandible length are found in 10.8-11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 0 publications
4
51
0
Order By: Relevance
“…In particular, plant pollen and macrofossils recovered from various places in the Carpathians showed that coniferous and broad-leaved trees were part of the local full-glacial environment (8,9). This finding is supported by evidence from animal fossils, which provide records of woodland species of small mammals in deposits from the last glaciation in the Carpathians (10,11). Furthermore, divergent mtDNA sequences from extant Carpathian populations of several temperate vertebrate species, including amphibians (12,13) and fish (14,15), indicate the maintenance of separate lineages that may have persisted in the Carpathians during the last glaciation.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…In particular, plant pollen and macrofossils recovered from various places in the Carpathians showed that coniferous and broad-leaved trees were part of the local full-glacial environment (8,9). This finding is supported by evidence from animal fossils, which provide records of woodland species of small mammals in deposits from the last glaciation in the Carpathians (10,11). Furthermore, divergent mtDNA sequences from extant Carpathian populations of several temperate vertebrate species, including amphibians (12,13) and fish (14,15), indicate the maintenance of separate lineages that may have persisted in the Carpathians during the last glaciation.…”
supporting
confidence: 72%
“…The Carpathian Mountains have been proposed as a possible refugial area for this species based on the fossil record. Bank vole fossils have been identified in deposits from the last glaciation in the Carpathian Mountains together with typical glacial assemblages and suggest that the species may have had a continuous presence in this region (10,11,18). We have collected mtDNA sequences from the Carpathians and adjacent regions ( Fig.…”
mentioning
confidence: 99%
“…Neither is the Italian peninsula currently considered as a recent refugium for the common shrew. Instead, there is accumulating evidence of glacial refugia in central or eastern Europe which could have been utilised by small mammals both from genetic data (Bilton et al 1998;Jaarola and Searle 2002;Brunhoff et al 2003), fossil data dating back to the LGM (Jánossy 1986;Nadachowski 1989;Markova et al 1995) as well as indications of full-glacial forests (Willis et al 2000). A refugium located in central or east Europe would have enabled a rapid recolonisation of northern territories.…”
Section: Discussionmentioning
confidence: 95%
“…The history of its settlement in central Europe is however complicated due to repeated range expansions during the Quaternary climate oscillations. The trace fossils indicate that the common hamster was present in Poland from the Eemian interglacial (Nadachowski 1989). The westward migration from the European steppe zone was probably via two routes: a northern route across the European plains, and a southern route to the Carpathian Basin (Neumann et al 2005).…”
Section: Introductionmentioning
confidence: 99%